Effectiveness of Laboratory Parameters as Morbidity and Mortality Indicators in Patients with Coronavirus Disease-2019 Admitted to the Intensive Care Unit - Leyla Kazancıoğlu; Başar Erdivanlı; Hızır Kazdal; Abdullah Özdemir; Tolga Koyuncu; Ayşe Hızal; Asiye Özdemir; İlkay Bahçeci; Şule Batcık; Tahir Ersöz (Türk Yoğun Bakim Derneği Dergisi)

(untitled)
Objective:Laboratory parameters may predict the severity and mortality of coronavirus disease-2019 (COVID-19). We investigated the relationship of laboratory findings obtained at admission and 72nd hour and mortality and morbidity of patients with pneumonia who were treated in two intensive care units.Materials and Methods:Chart data of 75 patients (March-May 2020) were retrospectively analysed. Patient characteristics and laboratory parameters were compared according to the presence of COVID-19 and mortality. Patients with COVID-19 were compared according to mortality and gender.Results:The mean patient age was 74.7±11.3 years. COVID-19 positivity was not associated with marked differences in laboratory values. Lung disease, bedridden status, worse renal function scores, and high C-reactive protein level was more often observed in non-survivors (p<0.05). A decline in D-dimer level was more apparent in survivors; the increase in ferritin and neutrophillymphocyte ratio was more apparent in non-survivors (not significant). Among patients with COVID- 19, women had higher mean platelet volume than men (p=0.033). The rise in ferritin level was more pronounced in men, whereas the rise in neutrophil-lymphocyte ratio and platelet-lymphocyte ratio was higher in women.Conclusion:In this geriatric cohort, chronic lung disease and bedridden status were the main determinants of mortality. Moreover, different patterns of inflammatory markers may help predict the severity of COVID-19.